Recent breakthroughs of non-thermal cold plasma food processing: A review - Muhammad Umair; Song Xun; Saqib Jabbar; Muhammad Abid; Muhammad Shahid Riaz Rajoka; He Zhendan (Carbohydrate Polymer Technologies and Applications)
Polymers are extensively utilized in industrial and (bio) medical applications for eco-friendly packaging solution, but they are typically unsuitable for usage owing to their moisture sensitivity, low surface free energy and barrier properties. The use of atmospheric cold plasma (ACP) technology to mitigate the surface characteristics of biopolymers is a fast developing research area and has a lot of appeal. This review explores the emerging field of surface modification of biodegradable polymers with ACP for food packaging application, presenting them as potential one avenue sustainable solution for biodegradable, better moisture barrier properties, and its food compatibility with minimal environmental impact and improved functionality. Key topics addressed included structural and functional properties of a biopolymer surface, topographical changes, the concerns regarding the critical outcome on the polymer qualities and highlighting the potential of ACP in cleaning and deposition biopolymers to reduce environmental impact and preserve food quality. Further, it delves recent advancements in food packaging technology that have made it possible to preserve both food and food packaging. There have been few investigations into the impact of cold plasma on the polymers used in packaging materials. However, a significant gap has been identified in the field of biodegradable polymers used in the food industry. This, combined with concerns about petrochemical-based polymers' environmental impact, prompted researchers to investigate the effects of cold plasma on biodegradable polymers. This review lays groundwork for determining the effect of ACP on a number of food packaging applications, including primary, smart, and active packaging. The purpose of this study was to determine whether various packaging solutions were compatible with the ACP process characteristics of food decontamination operations.